Potential role of exosomes derived from the tumor microenvironment in tumor progression and treatment - Yu, Ying; Zhang, Wenjun; Wang, Kun (Frontiers in Oncology, 2026)
Exosomes are important intercellular communication substances that connect the intercellular communication between the tumor microenvironment and the premetastatic microenvironment during tumor progression. By carrying different regulatory substances, such as proteins, cytokines, nucleic acids, etc., to regulate tumor progression, including angiogenesis, invasion, metastasis, drug resistance and other aspects. In addition to their potential as diagnostic markers, exosomes can also be used as excellent drug delivery carriers. Due to their excellent targeting and histocompatibility, exosomes have considerable application prospects in tumor therapy. This reviews recent studies on tumor-related exosomes, summarizes the mechanisms of intercellular communication and regulation of exosomes in tumor microenvironment and pre-metastasis microenvironment, and summarizes the current research progress on exosomes in tumor therapy.